Industrial inspection of marble tiles - Bakolias, C.; Skarlatos, Dimitrios (My University, 2010)
The main scope was the development of support code for a marble tile inspection machine. Marble tiles running on a conveyor belt are captured with a linear CCD camera, and the images are being used for geometrically inspection within 300 msec, which is the available time until the tile reaches the selection mechanism right after the inspection chamber. Supporting algorithm should be fully functional, fast, full proof, and should be easily modifiable to accommodate tiles of any size and colouring. Since the whole system would be fully automated and used by inexperienced personnel, the algorithm should self-check for CCD array problems, such as burned pixels, dirt on the sensor itself or on the housing. The absence of marble tiles on the belt or totally misplaced tiles should also be accounted for and alert the users. The algorithm also supports storage on a database of a cropped image of the tile in a predefined image size. The proposed algorithm is taking advantage of the constrained environment to extract edge pixel and form edge line using robust least squares. The corners of the tile are detected using line intersection, which in turn are used to calculate the geometrical characteristics. The final tile cropping is being done using projective transformation to adjust rotation, misalignments and size uniformity in the created image tile database.
Keywords: Algorithms; Belt conveyors; Charge coupled devices; Edge detection; Extraction; Marble; Pixels; Edge extraction; Least Square; Line extraction; Linear CCD; Real time; Inspection